Peer effects of ambition - Philipp Albert; Dorothea Kübler; Juliana Silva-Goncalves (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2019)
Ambition as the desire for personal achievement is an important driver of behavior. Using laboratory experiments, we study the role of social influence on ambition in two distinct domains of achievement, namely performance goals and task complexity. In the first case, participants set themselves a performance goal for a task they have to work on. The goal is associated with a proportional bonus that is added to a piece rate if the goal is reached. In the second case, they choose the complexity of the task, which is positively associated with the piece rate compensation and effort. In both cases we test whether observing peer choices influences own choices. We find strong evidence of peer effects on performance goals. In contrast, we find no support for peer effects on the choice of task complexity.
Keywords: C91; D83; D91; I24; M5; 330; peer effects; ambition; goal setting; task difficulty; laboratory experiment